2016
DOI: 10.1097/aog.0000000000001567
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Surgical Care Among Women With Endometrial Cancer

Abstract: Most U.S. women with endometrial cancer continue to be treated with open hysterectomy surgery despite increased complication rates and financial costs associated with this approach. A disparity in endometrial cancer surgical care exists that is affected by patient race and hospital geography and cancer volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 13 publications
2
50
0
2
Order By: Relevance
“…2 In the USA, women of color experience higher rates of severe maternal morbidity [3][4][5][6][7] and death during and after pregnancy. Although race/ ethnicity is known to be associated with disparate outcomes in nonobstetric hysterectomy care, 8,9 the relationship between race/ethnicity and peripartum hysterectomy 6,[10][11][12] or its related outcomes 10 is not well-explored. Recent publications focus on differences in outcomes after peripartum hysterectomy based on hospital characteristics, without examining disparities among minority groups, 13,14 or they have combined peripartum hysterectomy with other maternal morbidity outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2 In the USA, women of color experience higher rates of severe maternal morbidity [3][4][5][6][7] and death during and after pregnancy. Although race/ ethnicity is known to be associated with disparate outcomes in nonobstetric hysterectomy care, 8,9 the relationship between race/ethnicity and peripartum hysterectomy 6,[10][11][12] or its related outcomes 10 is not well-explored. Recent publications focus on differences in outcomes after peripartum hysterectomy based on hospital characteristics, without examining disparities among minority groups, 13,14 or they have combined peripartum hysterectomy with other maternal morbidity outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that high-grade endometrial cancer cases who received care at moderately high-, intermediate-, or low- volume facilities were less likely to be surgically staged than those who received care at high-volume facilities [21]. Similarly, another study found that endometrial cancer cases who received care at rural, low-volume hospitals were more likely to have open surgery, rather than minimally invasive surgery, which is the recommended surgical procedure [38]. This study also found that open surgeries were less likely to have lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…68 Epidemiologic analysis of early-stage endometrial cancer cases during 2012-2013 from the National Inpatient Sample database showed that patients were less likely to undergo MIS in rural compared with urban areas (OR: 14.34, 95% CI: 9.66-21.27), government compared with nonprofit hospitals (OR: 1.66, 95% CI: 1.15-2.39), and black race (OR: 1.46, 95% CI: 1.30-1.65). 71 Fader et al 35 Despite higher costs of robotic surgery on a single case level, long-term cost reductions from the decrease in laparotomy rates and associated postoperative complications are beneficial in this population that is already characterized by obesity and other comorbidities. The published data signifies that MIS is safe and clinically effective for the treatment of earlystage endometrial cancer and should also be considered for patients with high-risk histology.…”
Section: Specific Disease-based Gynecologic Outcomes With Robotic Surmentioning
confidence: 99%